Low cost capacimeter, metrological analysis. (July 2016) - Kramar, M G; Souza, R U; Machado, V
Abstract: Daily, for electronic professionals, a common need is to measure a capacitance from a capacitor. Often this measurement requires expensive equipments, not portables. This paper describes the development of an electronic circuit capable of measuring capacitance within the range of 100 nF up to 1 mF, providing a reliable and affordable system. Measures had been taken and metrological analyzes were performed on the experimental data. Also, the system theoretical model was evaluated in order to compare the behavior of both: practical and modeled system, investigating the availability of further improvements. A functional circuit with uncertainties compatible to those, provided for the theoretical model was developed. The developed system proved to be accurate, inexpensive and suitable for portable measurements.